2013
DOI: 10.1007/s11302-013-9385-0
|View full text |Cite
|
Sign up to set email alerts
|

CD39-mediated effect of human bone marrow-derived mesenchymal stem cells on the human Th17 cell function

Abstract: This study investigated the immune-modulatory effects of human bone marrow-derived mesenchymal stem cells (hBMSCs) on human Th17 cell function through the CD39-mediated adenosine-producing pathway. The suppressive effects of hBMSCs were evaluated by assessing their effects on the proliferation of Th17 cells and the secretion of interferon (IFN)-γ and interleukin (IL)-17A by Th17 cells with or without anti-CD39 treatment. Changes in CD39 and CD73 expression on the T cells with or without co-culture of hBMSCs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 29 publications
1
36
1
Order By: Relevance
“…Adding a parenthesis to this subject, CD39 expression by MSCs has been subject to conflicting observations [177]. In contrast to our observations [175] and others [178,179], some authors describe a lack or low CD39 expression by MSCs [176,180]. In our view, this might be due to specific experiment design or to antibody variation.…”
Section: Mscs and Adenosinecontrasting
confidence: 91%
See 1 more Smart Citation
“…Adding a parenthesis to this subject, CD39 expression by MSCs has been subject to conflicting observations [177]. In contrast to our observations [175] and others [178,179], some authors describe a lack or low CD39 expression by MSCs [176,180]. In our view, this might be due to specific experiment design or to antibody variation.…”
Section: Mscs and Adenosinecontrasting
confidence: 91%
“…Since NK-cells already express CD39, which is kept in stable levels in the presence of MSCs, CD73 completes the adenosine framework, and in fact, NK-cells themselves end up producing adenosine and inactivating themselves [181]. Such event was also observed in Th-17 cells, which increased their CD39 and CD73 upon coculture with MSCs and had their activation suppressed by adenosinerelated mechanisms [179].…”
Section: Mscs and Adenosinementioning
confidence: 92%
“…However, the frequency of adenosine receptor expression has yet to be determined for MSCs. CD39 may be expressed on a small subset of MSCs, but its activity can also be contributed by its presence on other cells that lie adjacent to MSCs [43][44][45]. Thus, this trio of cell surface molecules exert localized functions that include: anti-inflammatory activities, immuno-supressive activities, and pro-angiogenic activities.…”
Section: The Curtainmentioning
confidence: 99%
“…Thus, new studies are needed to assess the role of hypoxia in regulating the function of this molecule on MSC function. In vitro studies have shown that mixing human or mouse MSCs with Th1 or Th17 cells results in the upregulation of adenosine production by MSCs [43,[45][46][47]. Further, adenosine produced in this manner suppresses the functional activity of these T-cells and may induce apoptosis in these populations.…”
Section: The Curtainmentioning
confidence: 99%
“…Co-cultures of MSC suppress proliferation of stimulated mononuclear cells (33) or T-lymphocytes (34) (35) and Fas ligand-mediated apoptosis of T-cells (36). The interaction of T1 or T17 lymphocytes upregulates adenosine production by MSC that suppresses these lymphocyte populations (37) (38) and leads to new blood vessel formation through stimulation of vascular endothelial growth factor (39). The interaction of MSC and monocytes results in their production of IL-10 and an anti-inflammatory phenotype (40).…”
Section: Mode Of Action Of Msc Supplementationmentioning
confidence: 99%